Introduction of minimally invasive surgery for distal and total gastrectomy: a population-based study. Issue 3 (March 2019) - Gertsen, E.C.; Brenkman, H.J.F.; Seesing, M.F.J.; Goense, L.; Ruurda, J.P.; van Hillegersberg, R.; ,
Abstract: Background: Minimally invasive gastrectomy has been introduced in Western populations during the last decade. As minimally invasive distal gastrectomy (MIDG) versus total gastrectomy (MITG) are procedures with a different complexity, outcomes may differ. The aim of this population-based cohort study was to evaluate the safety of MIDG and MITG. Materials and methods: All patients who underwent potentially curative gastrectomy for gastric adenocarcinoma were included from the Dutch Upper GI Cancer Audit (2011–2016). Propensity score matching was applied to create comparable groups of patients receiving open distal gastrectomy (ODG) versus MIDG and open total gastrectomy (OTG) versus MITG, using patient and tumor characteristics. Postoperative outcomes and short-term oncological outcomes were appraised. Results: Of the 1970 eligible patients, 1138 underwent distal gastrectomy and 832 underwent total gastrectomy. For distal gastrectomy, 390 ODG were matched to 288 MIDG patients. Although overall postoperative morbidity and mortality were similar, patients who underwent MIDG encountered less intra-abdominal abscesses (4% vs. 1%, p = 0.039) and wound complications (6% vs. 2%, p = 0.021). The median hospital stay was shorter after MIDGs (9 vs. 7 days, p < 0.001). For total gastrectomy, 323 OTG patients were matched to 258 MITG patients. Overall postoperative morbidity, mortality and hospital stay were similar, whereas the anastomotic leakage rate was higher after MITGs (11% vs. 17%, p = 0.030). Short-term oncological outcomes between both groups were equal for distal and total gastrectomy. Conclusion: Benefits of MIG during the early introduction were demonstrated for distal gastrectomy but not for total gastrectomy. An increased anastomotic leakage rate was encountered for MITG.